2003
DOI: 10.1017/s1357729800053339
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality of Boer goat kids and Mutton Merino lambs 2. Sensory meat evaluation

Abstract: The meat palatability, water-holding capacity, colour and shear force values of 32 Boer goat (BG) kids and 32 South African Mutton Merino (MM) lambs were investigated. Two pelleted diets (offered to 16 animals per species) with either a low (LE, 9·9 MJ/kg dry matter (DM)) or a high (HE, 12·1 MJ/kg DM) metabolizable energy level were given to the animals for either 28 or 56 days. Thereafter the animals were slaughtered, the meat cooked and presented to a trained sensory panel. Organoleptically, a difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
3
15
1
Order By: Relevance
“…The kid meat was significantly lighter and less yellow than the lamb meat (Table 6). These results are in agreement with Sheridan et al (2003), who analyzed the LM for color measurement of Boer goat kids and mutton merino lambs finished under feedlot conditions. In the present study, the redness of muscle was not influenced by species (Table 6), although goat meat color tends to be darker red than lamb and mutton meat (Babiker et al, 1990;Sheridan et al, 2003).…”
Section: Meat Quality Attributessupporting
confidence: 91%
See 1 more Smart Citation
“…The kid meat was significantly lighter and less yellow than the lamb meat (Table 6). These results are in agreement with Sheridan et al (2003), who analyzed the LM for color measurement of Boer goat kids and mutton merino lambs finished under feedlot conditions. In the present study, the redness of muscle was not influenced by species (Table 6), although goat meat color tends to be darker red than lamb and mutton meat (Babiker et al, 1990;Sheridan et al, 2003).…”
Section: Meat Quality Attributessupporting
confidence: 91%
“…There are inherent differences between the 2 species. Goat meat tends to be darker red (Sheridan et al, 2003) and less tender than sheep (Webb et al, 2005) and is characterized by a low intramuscular and subcutaneous fat content (Babiker et al, 1990;Mahgoub and Lodge, 1998) at comparable ages and sexes. Thus, the aim of this study was to compare the carcass composition and meat quality attributes of equally mature kids and lambs raised under similar environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Costa et al [19] found that the inclusion of cactus pear has no-effect on ram meat tenderness. The current result of tenderness is near to that found by Swan et al [54] (9.1 kgf) and lower than reported by Sheridan et al [55] (11.1 kgf) for Semimembranosus of Boer goat. Chevon is more hardness than sheep meat because it is characterized by a high collagen content with a low solubility, high fibrous residues, and larger and ticker myofibrils [3].…”
Section: Meat Qualitysupporting
confidence: 56%
“…Typically, sheep have less collagen content than goats, and collagen solubility differs between breeds of small ruminant (Schönfeldt et al 1993). Sheridan et al (2003) found that goat and lamb had distinct, species-specific flavors. In our study, the flavor and overall acceptability of lamb received medium scores; however, that study and our work differed in the age at which the lambs were slaughtered.…”
Section: Effects Of Breed and Species On Consumer Preferencesmentioning
confidence: 99%
“…In our study, the flavor and overall acceptability of lamb received medium scores; however, that study and our work differed in the age at which the lambs were slaughtered. In Sheridan et al (2003), lambs were finished in a feedlot for 1 or 2 months. Then, a dam's milk diet and the early age at slaughter appear to have had a greater influence on flavor and overall acceptability than did specie per se.…”
Section: Effects Of Breed and Species On Consumer Preferencesmentioning
confidence: 99%